The great subtraction : a brief account of select work by Giovanni Anselmo, Elisabetta Benassi, Gino De Dominicis, Francesco Matarrese, Marisa Merz, Luigi Ontani, Cesare Pietroiusti, Michelangelo Pistoletto and Emilio Prini - Guercio, Gabriele (Brussels : ASA Publishers, 2011)
Since the 1960s artists from various countries have positioned themselves increasingly within a system of art that is now global in its reach. However, Italian artists in particular have, with some exceptions, resisted expressing a certain putative artistic "Italian-ness," thus undermining the global system's tendency to identify artists, artworks, and movements according to nationality. The expression "Italian art" names quite an impervious referent: it exists in a kind of limbo, perpetually suspended between abysmal default and epiphanic excess, its identity as a subject neither ascertained nor denied. Italian artworks therefore neither correspond to a preexisting array of local attributes nor resonate with a discernible web of global meanings.
boek
Keywords: Anselmo, Giovanni; Benassi, Elisabetta; De Dominicis, Gino; Matarrese, Francesco; Merz, Marisa; Ontani, Luigi; Pietroiusti, Cesare; Pistoletto, Michelangelo; Prini, Emilio, -- 1943-